Mechanical and impact performance of oil palm trunk fiber composites for crash box applications - Sukarno, Sukarno; Suci, Indah Melati (Jurnal Polimesin, 2025)
The increasing demand for lightweight and sustainable materials in automotive safety components has driven interest in natural fiber composites. Abundant oil palm trunk waste in South Kalimantan presents a promising, low-cost source for composite reinforcement. This study aims to analyze the crashworthiness performance of crash box structures using oil palm trunk fiber composites as an environmentally friendly alternative material. The research method involved the fabrication of composite specimens with fiber orientations of 30°, 60°, and 90°, using epoxy resin as the matrix. Mechanical testing included tensile tests based on ASTM D638-02 and Charpy impact tests based on ASTM D6110. The tensile test results showed that fiber orientation significantly affects the mechanical properties of the composites. The 60° orientation exhibited the highest tensile strength and elastic modulus, while the 30° orientation demonstrated the highest elongation, indicating better ductility. The 90° orientation showed intermediate performance but tended to be brittle. The impact test results revealed that the 60° fiber orientation had the highest toughness in absorbing impact energy, whereas the 30° and 90° orientations displayed lower toughness. Overall, the 60° fiber orientation of oil palm trunk composites shows potential for crash box applications, as it provides a balance between strength and toughness, although its brittleness still requires further consideration.